Measuring Price Competitiveness for Industrial Country Trade in Manufactures. (IMF Working Papers; Working Paper ;, 1987)
This paper describes the methods used by the Research Department to construct the indicators of price competitiveness, or real effective exchange rates, published for 17 industrial countries in International Financial Statistics. The weighting scheme used to construct these indicators is derived from a disaggregated system of demand equations encompassing trade relations in bilateral and third-country markets. Other commonly used trade-weighting schemes are shown to be special cases of the more general and less restrictive competitiveness weights. Differences in the measurement of relative price changes using indices based on other weights are explained by the greater informational content of the competitiveness weights.